Cassava technology transfer in Indonesia - Dimyati, Ahmad (International Center for Tropical Agriculture, 1995)
Economically and politically, cassava is considered less important than rice, soybean and maize. Government's investment in the infrastructure and institutions for cassava extension and technology transfer is far less than those for the three major food crops. The infrastructure for varietal dissemination is relatively better than that for other components of technology. Due to the lack of such infrastructure and institutions, non-conventional ways of technology transfer take place and play a major role. The role of private companies in delivering planting material of newly released varieties is quite significant. The same role for transferring cassava flour processing technology has not happened due to socio-economic barriers. Despite the obligatory role of the Directorate General of Food Crop Agriculture to verify and disseminate the production technology, farmers can get the benefit of accessing directly to the source of technology by participating in the large-scale on-farm research, development research, and research-extension linkage activities. Corrections in the institutional set-up and mechanisms of technology transfer will be the appropriate way to enhance the effectiveness and efficiency of the technology transfer process. The establishment of knowledge centers or fora at the provincial or district levels, where farmers, researchers and extensionists work integratedly to formulate location-specific technologies, is viable and compatible with the current integration of Agricultural Information Centers into the Agency for Agricultural Research and Development